Influence of acute high altitude exposure and short-term acclimation on platelet-associated parameters in healthy young man - Jing-bin KE; Jia-bei, LI; Ji-hang, ZHANG; Shi-zhu, BIAN; YANG, Jie; LIU, Chuan; CHEN, Can; ZHANG, Chen; YU, Jie; JIN, Jun; HUANG, Lan (Jie fang jun yi xue za zhi, 2018)
Objective To explore the effect of high altitude exposure and short-term acclimation on the platelet-associated parameters by studying the changes of platelet-associated parameters in healthy young man. Methods Four hundred and sixty- two young men were recruited from Chengdu (the elevation of 500m) during Jun. 2012 to Aug. 2013 according to the inclusion and exclusion criteria, of which 193 had been living in Chengdu (plain group), and 269 flew from Chengdu to Lhasa (3700m) in 2 hours, and then 147 of them were exposed in the high altitude for 1 day (acute high altitude exposure group), and another 122 for 7 days (short-term acclimation group). The demographic data were collected and the blood routine and platelet-associated parameters were measured of all the participants, and then the information collected were compared between the 3 groups. Results Compared to the plain group, the platelet count (PLT), platelet distribution width (PDW) and plateletcrit (PCT) reduced and the mean platelet volume (MPV) incr